Nidification strategies and disease risk in necrophagous Scarabaeinae - Fialho, Verônica Saraiva (2017)
Decomposition of carcasses releases large amount of nutrients and moisture into the ground. These nutrients attract many consumers and promote microbial growth. Besides feeding, many insects use carcasses for breeding. As carcasses are environments full of microorganisms, these insects must have defensive strategies to avoid or minimize the threats, such as the risk of infection, that arise from exploiting this resource. Little attention has been given to the selective pressures posed by entomopathogens and opportunistic microbes present in this environment on necrophagous insects such as a number of Scarabaeinae beetles. Thus, we evaluated the effect of the carcass decomposition over opportunistic microorganisms and potential entomopathogens. We show that decomposition increases the abundance and activity of these microorganisms, decreasing the longevity of beetle larvae placed in contact with the soil near to the carcass. These results highlight the probabilities of infection in exploiting carcasses. Thus, it is possible that reallocating food far away from the carcass may be a defensive behaviour as much against competitors (as previously proposed) as against infection risk (as indicated here). Additionally, we studied the abdominal glands of the paracoprid Scarabaeinae Coprophanaeus (Megaphanaeus) bellicosus (Olivier 1789), due to their elaborated nidification behaviour. Female C. bellicosus construct a deep nest, collect and prepare the food for their offspring, modelling it in an ovoid mass covered by a bulky soil layer, supposedly using abdominal secretions. The class-3 exocrine gland cells present in the abdomen of these beetles produce a proteinaceous secretion with no antibiotic activity. This latter result may explain the energetic investment in the nest construction in a safe place, far from the carcass, and extremely deep in the soil.